Division of Inheritance Property for Women in the Qur'an Persfective Wahbah Az-Zuhaili (Analysis Study of Heritage Division in Ubar Village, Padang Bolak Julu District, North Padang Lawas Regency - Rahmad Husein Siregar; Mardian Idris Harahap (al-Afkar, Journal For Islamic Studies, 2025)
The distribution of inheritance for women in the Koran is still a topic of debate among scholars. This research aims to analyze the distribution of inheritance for women in the Koran from the perspective of Wahbah az-Zuhaili. The research results show that the distribution of inheritance for women in the Koran must be carried out based on the principles of justice and equality. The people in Ubar Village, Padang Bolak Julu District, North Padang Lawas Regency, still have a patriarchal view in the division of inheritance. The aim of this learning is to analyze Wahbah az-Zuhaili's views on the distribution of inheritance for women in the Koran, analyze the views of the community in Ubar Village regarding the distribution of inheritance for women, identify factors that influence the distribution of inheritance for women in Ubar Village. Learning Methods are research methods: qualitative research with a content analysis approach. Data source: The type of data used is primary data obtained through the interpretation of al-Munir books by Wahbah az-Zuhaili, interviews with people in Ubar Village. Data analysis techniques: content analysis and thematic analysis. The finding/learning result is that the distribution of inheritance for women in the Koran must be carried out based on the principles of justice and equality. The people in Ubar Village still have a patriarchal view in the division of inheritance. Factors that influence the distribution of inheritance for women in Ubar Village are tradition, culture and religious knowledge.